The nomenclature of scientific specialties and the new model of award of academic degrees: Russian experience - Svetlana V. Narutto (Правоприменение, 2019)
The subject of the article is legal regulation of award of academic degrees in Russia after the reform that let universities and scientific organization award academic degrees independently, without centralized state control over this process.The main aim of the article is to confirm or disprove the hypothesis that universities that have received the right to self‐award academic degrees, should have the ability to determine the list of scientific specialties.The methodology of the study includes analysis, synthesis, description as well as formal‐ legal method and interpretation of legal acts.The main results and scope of their application. Impossibility of application their own nomenclatures of scientific specialties by educational and scientific organizations that have received the right to independently award academic degrees is justified. Not only federal regulatory legal acts interrelated with the nomenclature of specialties, for which scientific degrees are awarded, but also local legal acts of organizations that regulate the designated issues in different ways were analyzed. The criteria of systematization in the nomenclature of scientific specialties by levels are not set in a single key, which can cause problems in determining the subject and methods of research and expert evaluation of the thesis. Organizations fix procedural issues of examination of dissertations, as well as other issues related to the formation of dissertation councils and their work, the award of academic degrees, the issuance of diplomas, in local regulations that create conditions for the decentralization of legal support for the implementation of state policy in this area. The applicant for an academic degree has the right to prepare a dissertation and pass candidate examinations in a scientific specialty in any organization that meets the established requirements. Then the applicant for an academic degree has the right to apply to the organization, which has the right to self‐award of academic degrees. However, if the specialties which are absent in the official state nomenclature were established in this organization, the rights of applicants will be broken, and they will be put in unequal conditions with those applicants who passed candidate examinations in this organization.Conclusions. The universities that have received the right to self‐award academic degrees, should have the ability to determine the list of scientific specialties, as this would entail violation of the rights of applicants for academic degrees.